Banana King / Abu Sopian Karate ... [et al.] - Karate, Abu Sopian; Lampok, Justin; Abd Rahim, Rahmah; Durahman, Siti Safiah (2011)
Fundamentals of entrepreneurship as a part of our course subject is designed to provide students with knowledge and exposure in the field of small business and entrepreneurship as well as introducing students with some of the basic techniques and tools that can be used by entrepreneurs in managing their businesses. Apart from that, this course will guide us in facing a very challenging but rewarding career in the future which are not only theoretical but conceptual aspects of entrepreneurship and the crucial hands-on knowledge that will facilitate our understandings of entrepreneurship. The business that we would like to propose is a relaxing cafe concept that provides services in the form of food and beverages based on banana. We chose bananas as the main products in foods and beverages that we offer because banana is a fruit that was popular among local communities, particularly areas of Kota Kinabalu. Among the foods derived from bananas that we provide is a banana cake, dipped banana and banana chips. We also provide juice bananas as the main drink of choice for our customers. The place that we choose to open up our cafe is at the Suria Sabah that located in a centre of city of Kota Kinabalu. Our business's promise of affordable prices and provides a comfortable environment in our store for our customers' satisfaction. We hope to obtain and play an important part in the fast food industry in Sabah and have a healthy competition between other international brands. This will help us in obtaining useful knowledge and worthwhile experience in the competitive business world. Thus, bringing our Malaysian brand to the eye of the world. We also hope that our objectives and visions could be achieved with our teamwork effort and shared knowledge.